【世界大學排名系列報導】2024 QS世界大學排名陽明交大第 217 名 位居國內第二 - 校務大數據研究中心 (國立陽明交通大學, 2023)
2024 QS世界大學排名陽明交大第 217 名 位居國內第二
【World University Ranking Series Report】2024 QS World University Rankings, NYCU is ranked 217th, making it the 2nd highest-ranked university in Taiwan